2012
DOI: 10.1161/hypertensionaha.112.194340
|View full text |Cite
|
Sign up to set email alerts
|

Short- and Long-Term Blood Pressure Variability

Abstract: It has long been known that blood pressure (BP) is characterized by an array of spontaneous variations.1 That is, BP values vary markedly within the 24 hours because of day-night changes but also because of differences among hours, minutes, and even adjacent beats. They also show variations over more prolonged periods because of differences among days, months, and seasons, 2 also with a trend for systolic BP to increase over the years and for diastolic BP to display an age-related biphasic change. 3This articl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
121
0
8

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 231 publications
(140 citation statements)
references
References 53 publications
4
121
0
8
Order By: Relevance
“…Blood pressure measurement 5 BP was measured using standardized procedures and conditions, with validated automatic devices (Omron M6) and appropriate-sized cuffs. Trained observers measured each participant's BP during a home visit: three measurements were taken at two-minute intervals after resting for five minutes in a seated position.…”
Section: Study Variablesmentioning
confidence: 99%
See 2 more Smart Citations
“…Blood pressure measurement 5 BP was measured using standardized procedures and conditions, with validated automatic devices (Omron M6) and appropriate-sized cuffs. Trained observers measured each participant's BP during a home visit: three measurements were taken at two-minute intervals after resting for five minutes in a seated position.…”
Section: Study Variablesmentioning
confidence: 99%
“…3,4 BP not only exhibits large circadian variations in terms of changes between day and night but also changes from minute-to-minute and hour-to-hour in both hypertensive and normotensive patients. 5 Thus, non-invasive 24-hour ABPM is a robust method to assess short-term BP variability within 24 hours. 6 Most studies have found that high 24-hour BP variability is associated with organ damage and may contribute to cardiovascular risk prediction, over and beyond mean BP.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Twenty-four-hour ambulatory BP monitoring is a widely used method evaluating short-term BPV. 4 Hypertension has a well-known association with ascending aortic dilatation (AAD) and dissection. 5 But there are no data regarding association between BPV and AAD in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…Na podstawie ABPM można uzyskać wiele dodatkowych pochodnych wskaźników [75--81]. Należą do nich: zmienność BP [75], poranny wzrost BP [76,77,81], ładunek BP [78] oraz ambulatoryjny wskaźnik sztywności tętnic (ambulatory arterial stiffness index) [79,80]. Jednak dotychczas nie wyjaśniono dodatkowej wartości predykcyjnej tych wskaźników i dlatego należy traktować je jako eksperymentalne, niemające jeszcze zastosowania w rutynowej praktyce klinicznej.…”
Section: Pomiary Ciśnienia Tętniczego Poza Gabinetem Lekarskim Lub Prunclassified